GEOSPATIAL MODELING OF LAND USE MANAGEMENT FOR SUSTAINABLE URBAN DEVELOPMENT IN KARU, NASARAWA STATE, NIGERIA (FULafia Journal of Science and Technology, 2016)
Land use management is a major challenge of urban development in Africa. Karu Area of Nasarawa State, a principal satellite town of the Federal Capital Territory, Abuja is the fastest growing city in Africa since the relocation of the Federal Capital from Lagos to Abuja in 1991. The proximity of the area to Abuja has attracted rapid economic and population growth with speed up urban expansion and poor living environment. This study used geospatial technology in Land use management of the area. Multi-Criteria Decision Analysisusing Euclidean distance and weighted overlay from spatial analyst tool of ArcGIS, supported by Analytical Hierarchical Process were used to assess the suitability of the area for urban development. The Land Use Act Cap 202 of 1990 and the Nigeria Urban and Regional planning Act of 1990 were adopted using buffering operation in ArcGIS to determine encroachment of buildings/structures into approved setback areas of water bodies and road network. The study revealed land acquisition through informal delivery, resulting to haphazard constructions, and encroachment of buildings/structures into the approved setback areas. In addition, the areas are prone to flooding and erosion. It is recommended that, urgent need for the use of geospatial technology for land acquisition and management be adopted for sustainable development of the area
Keywords: Land Suitability; Urban Expansion; Geospatial Modeling; Multi-Criteria Decision Analysis